Innovative Learning Design Development Training Based on Project Based Learning (PjBL) for Professional Teacher Education Program (PPG) Students Using the Zoom Platform - Lili Herawati Parapat; Arman Sofianus Gulo; Sahat Gokmatua Sihombing (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to improve the competence of pre-service teachers in developing innovative Project Based Learning (PjBL)-based instructional designs through online training using the Zoom platform. The participants of this program were 18 students of the Teacher Professional Education (PPG) Program. The training was conducted through several stages, including preparation, delivery of PjBL concepts, instructional design workshops, discussion sessions, feedback, and evaluation. Data were collected through observation, participant responses, and assessment of the instructional design products developed during the training. The results showed that the training positively improved participants’ understanding and skills in designing PjBL-based learning activities. Most participants demonstrated better ability to formulate learning objectives, develop project activities, design assessment instruments, and integrate technology into learning designs. The evaluation results indicated that 16 participants (88.89%) experienced significant improvement in their understanding and competence, while 2 participants (11.11%) still required further guidance, particularly in developing project assessment strategies. The use of the Zoom platform also supported effective interaction, collaboration, and knowledge sharing during the training process. It can be concluded that the implementation of online PjBL-based instructional design training effectively enhanced PPG students’ pedagogical competence and prepared them to create innovative, contextual, and student-centered learning experiences.